Aetiopathology of rheumatoid arthritis - Taylor, P; Mehta, P; Tull, T (2010)
Although the aetiology of rheumatoid arthritis remains unknown, there have been considerable advances in understanding the aetiopatho genesis in the last two decades. The role of genetic and environmental interactions in giving rise to immune dysregulation and the key cellular and cytokine mediators involved have been extensively studied. These insights have led to major advances in therapeutic options in the pharmacological management of this condition. © 2009 Elsevier Ltd. All rights reserved.